Respuesta :
Answer:
1. [tex]x=3[/tex]; 2. Domain: [tex]x>1[/tex] Range: all real numbers
Step-by-step explanation:
Let's find the solutions.
1. Solve the equation [tex]x=\sqrt{2x+3}[/tex] so:
[tex](x)^2=(\sqrt{2x+3})^2[/tex]
[tex]x^2=2x+3[/tex]
[tex]x^2-2x-3=0[/tex]
[tex]x1=\frac{-b+\sqrt{b^{2}-4ac}}{2a}[/tex]
[tex]x1=\frac{2+\sqrt{(-2)^{2}-(4*1*(-3))}}{2*1}[/tex]
[tex]x1=3[/tex]
[tex]x2=\frac{-b-\sqrt{b^{2}-4ac}}{2a}[/tex]
[tex]x2=\frac{2-\sqrt{(-2)^{2}-(4*1*(-3))}}{2*1}[/tex]
[tex]x2=-1[/tex]
Although we have two answers, remember that from the original equation the result of [tex]\sqrt{2x+3} > 0[/tex] is never negative. So -1 do not solve the equation.
In conlcusion, the equation is solved by x=3.
2A. Domains and ranges of f1(x) and f2(x)
[tex]f1(x)=ln(x+1)+ln(x-1)[/tex]
Using logarithmic property [tex]ln(a)+ln(b)=ln(a*b)[/tex] we have:
[tex]f1(x)=ln(x^2-1)[/tex] because:
[tex]ln(x)[/tex] is defined by [tex]x>0[/tex] then:
[tex]x^2-1>0[/tex]
[tex]x>\sqrt{1}[/tex] so the domain of f1(x) is [tex]x>1[/tex]
Now for the range:
[tex]f1(x)=ln(x+1)+ln(x-1)[/tex]
[tex]y=ln(x^2-1)[/tex]
[tex]e^y=x^2-1[/tex]
[tex]\sqrt{e^y+1}=x^2-1[/tex] notice that [tex]e^y+1[/tex] is always positive, so the range of f1(x) is all real numbers.
Be aware that although point number two of the problem mentioned two equations, f1(x)=f2(x) by logarithmic properties, so their domains and ranges are the same.
2B. Graph of f1(x) is attached. Because f1(x)=f2(x) both functions plot equal.
![Ver imagen dsavellanedaj](https://us-static.z-dn.net/files/d39/6b63577635b579e9e82f4e661fef7e93.jpg)